Biopreservation and Quality Enhancement of Fish Surimi Using Colorant Plant Extracts - Ahmed A. Tayel; Amira G. Bahnasy; Khaled E. Mazrou; Abdulrahman Alasmari; Haddad A. El Rabey; Shrifa A. Elboghashy; Amany M. Diab (Journal of Food Quality)
The biopreservation, flavoring, and coloration of foodstuffs, e.g., seafoods, with natural plant derivatives are major demands for consumers and overseers. Different colored plant parts, i.e., Hibiscus sabdariffa calyces, Curcuma longa rhizomes, and Rhus coriaria fruits, were extracted and evaluated as biopreservatives, antimicrobial and colorant agents for fish surimi from Oreochromis niloticus. All colorant plant extracts (CPEs) exhibited strong antibacterial activities against screened pathogens, Escherichia coli, Salmonella typhimurium, Staphylococcus aureus, and Pseudomonas aeruginosa. H. sabdariffa extract (HCE) was the most effectual antimicrobial CPEs. S. aureus was the most sensitive strain to CPEs, whereas S. typhimurium and P. aeruginosa were the most resistant strains. The exterior coloration of tilapia surimi with CPEs resulted in great bacterial count reduction in colored products; stored CPEs-colored surimi had enhanced sensorial attributes. HCE-exposed S. aureus indicated bacterial cell lyses in time-dependent manner. CPEs application as colorants and antibacterial and quality enhancing agents is recommended for seafoods’ biopreservation.